Waqf for Higher Education Institutions: A Conceptual Review - Abd Aziz, Nurul Aien; Sapuan, Noraina Mazuin; Muhamad Tamyez, Puteri Fadzline (Akademia Baru Publishing (M) Sdn Bhd, 2023)
Waqf has been an important instrument for the development of a nation, including in the higher education sector. In Malaysia, educational waqfstands as a potential tool that can help higher education institutions to reduce their dependency on government funding and improve their financial systems, infrastructure, and overall growth. Therefore, this study aims to contribute toward a better understanding of educational waqf implementation, particularly in Malaysian higher education institutions. The data were obtained using a qualitative research design through the formation of a theoretical framework via the analysis of journals, reports, and other documents. The findings are expected to provide valuable insights and suggestions on how to improve the performance and practice of waqf in Malaysian higher education institutions. It also offers several recommendations for further waqf research, particularly on its role to promote sustainability in higher education institutions.